Reliability Control Program Turbo Compressor 2222254-1 Nitrogen Generation System Pesawat Boeing 777-300ER di PT GMF AeroAsia Tbk - Riswanto, Cipto; Sofyan, Edi; Setiawan, Ferry; Noerachman, Edy; Nazarullah, Ibny (Universitas Al Azhar Indonesia, 2024)
The pilot report case of Garuda Indonesia's Boeing 777-300ER aircraft that occurred in 2018-2019 was mostly a case of Nitrogen Generation System (NGS) failure. The objective of this research is to identify the dominant factors causing failures in the NGS, evaluate the reliability and failure rates of its components, so as to obtain the estimated time the component may will fail, effective scheduled maintenance, maintenance method design, and the estimated primary cost of the maintenance program and reliability control program for its components within one year. The research methodology using Quantitative analysis’s Distribution Test - Life Data Analysis method combined with the Anderson Darling index of fit parameter of Least Square Curve Fitting approach and Qualitative analysis involves identifying potential root causes and the effects of failures, as well as determining maintenance actions using Failure Mode and Effect Analysis and Fault Tree Analysis. Based on the analysis results obtained, the dominant factor causing failures in the NGS for the period is the variation failure of Turbo Compressor. This component has a reliability of 28.73%, and the mean time to failure (MTTF) is 10,477.62 flight hours. As a result, the optimum interm action preventive maintenance interval (pre-modification) of Turbo Compressor NGS is 250 flight hours with a reliability of 90%, requiring preventive maintenance to be performed 35 times per year. The recommended maintenance action is a scheduled restoration task aimed at upgrading and modifying the Turbo Compressor. The estimated cost of scheduled maintenance for the Turbo Compressor NGS is Rp 2,632,913,890.35, and unscheduled maintenance costs Rp 5,354,508,684.42.Keywords – Reliability, Failure, Maintenance, Turbo Compressor, Nitrogen Generation System.